2020
DOI: 10.1002/jgf2.353
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision‐making ability of the patient receiving home medical care

Abstract: Background Patients' decision‐making ability is a substantial barrier to end‐of‐life conversations with doctors. This study aimed to examine factors influencing this ability. Methods Altogether, 914 doctors from Japanese home care supporting clinics providing home medical care as of February 2019 participated in this study. Data were collected through an anonymous mailed survey between April and May 2019. Results Stepwise multiple linear regression analysis of factors influencing patients’ decision‐making abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…26) Another of our results also suggested that family structure differences can affect their end-of-life preferences. 31) Thus, the family has some influence on the end of life care in Japan.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…26) Another of our results also suggested that family structure differences can affect their end-of-life preferences. 31) Thus, the family has some influence on the end of life care in Japan.…”
Section: ⅳ Discussionmentioning
confidence: 99%